Injuries to the hip in tennis players - Safran, M. R. (Medicine and Science in Tennis, 2006)
Hip injuries in tennis players have received more interest and attention lately. This is partly due to the apparent increased incidence of hip injuries in tennis players; at least an increase recognition of these injuries. The etiology of increase hip pain is unclear though many have attributed it to the open stance strokes that are so common in today's tennis game. While there are a lot of injuries to the hip that are musculotendinous in origin, such as strains and pulls, the adductors, the rectus femoris, the hamstrings and hip flexors, in addition to the recent recognition of the "sports hernia" and the long history of low back injuries and sacro-iliac joint dysfunction in tennis players, this articles focuses on the role of arthroscopy and intraarticular pathology in tennis.